KONDISI SOSIAL BUDAYA DAN EKONOMI MASYARAKAT YANG MEMANFAATKAN KAWASAN EKOSISTEM MANGROVE DI KAMPUNG BUKISI KABUPATEN JAYAPURA - Pirhel, Pirhel; Tuhumena, Lolita; Maruayana, Yan (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background : Mangroves are plants whose natural habitat is in coastal areas, so they absolutely need the role of coastal communities, who need empowerment in the implementation of mangrove management. Therefore, the sustainability of coastal areas will be maintained because of conservation activities, as well as they can obtain socio-economic benefits. Along with the increase in population and the high needs of the community, the high level of utilization of mangrove resources has resulted in a high level of utilization of mangrove resources. On the other hand, damaged natural resources, because they are not taken care of by the surrounding community, and are not taken care of by the surrounding community, can hardly meet the needs of the community in Bukisi Village. The purpose of the research is to examine the social, cultural and economic conditions of the people living around the mangrove ecosystem area in Bukisi Village, Yokari District, Jayapura Regency. Method: The research methods used were qualitative and quantitative descriptive methods as well as an overview of social, cultural and economic conditions in the utilization of mangrove ecosystems in Bukisi Village and 35 communities who were used as respondents. Results: Respondents were dominated by men, productive age 26-35 years, predominantly elementary school educated, fishermen, with an income of IDR 1,500,000 - IDR 2,500,000. Socio-economic characteristics illustrate that respondents who utilize the mangrove ecosystem are residents who live around the area and there are sacred places around the mangrove ecosystem area, so that no one is allowed to carry out activities in sacred locations. People in Bukisi village often use the mangrove ecosystem area to look for fish, shellfish, shrimp, crabs and even for firewood. Conclusion: Sustainability management strategies that are prioritized in terms of social, cultural and economic conditions as well as the role of stakeholders who are the most important actors in mangrove forest management in Bukisi Village, Yokari District, Jayapura Regency.